Analysis of Secondary Metabolites as Potential Phytoalexins, Their Secretion Sites and Proposed Resistance Markers to Vascular Streak Dieback in Theobroma cacao L. - Teguh Iman Santoso; Muhammad Miftahudin; Yohana C Sulistyaningsih; Suryo Wiyono (Indonesian Coffee and Cocoa Research Institute, 2017)
Study on resistance mechanism to vascular-streak dieback (VSD) disease in cacao (Theobroma cacao L.) is limited due to the lack of fungal spores for artificial inoculation. This research was conducted to study the production of secondary metabolites that appear to be evidence of defense signaling in resistant clone of Sca 6 and susceptible clone of TSH 858 to Ceratobasidium theobromae natural infection. A fungal staining method was employed to detect C. theobromae hyphae at early infection stages, before VSD symptoms appear. Metabolite profiling was analyzed using pyrolysis gas chromatography mass spectrometry (Py-GCMS) at pre-, early and late stages of C. theobromae infection. Histochemical and anatomical characteristics of both healthy and infected leaves were also observed to identify the accumulation sites of secondary metabolites on and in cocoa leaf tissues. The results confirmed that fungal staining using trypan blue can detect early stages of C. theobromae infection; at the 14th week (on susceptible seedlings) and the 18th week (on resistant clones), following placement of the seedlings under infected cacao plants. Phenylpropanoid biosynthesis, terpenoid biosynthesis, environmental information processing signal transduction pathways, and aromatic biodegradation were detected as important metabolite pathways during defense mechanism. I-limonene (terpenoid), p-ethylguaiacol (phenols) and 2.3 dihidrobenzofuran (heterocyclic compounds) were proposed as an active defense produced by the host after infected by pathogen mainly on late infection of C. theobromae. Terpenoid and phenol compounds were accumulated on the glandular trichomes, idioblast of upper and bottom epidermis, phloem vessel and cortex idioblast of cacao leaves. Epidermis thickness of resistant clone was significantly greater than that of susceptible clone on both surfaces. Leaf epidermis tissue and the accumulated compounds in epidermis idioblast may act as the physical and biochemical markers of cocoa resistance to VSD.